Our Long Heritage : Pages From the Books our Founding Fathers Read - Clough, Wilson Ober, 1894-1990 (Book collections on Project MUSE., 1955)
Our Long Heritage was first published in 1955. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. This collection of readings, selected from the books and documents that were the major sources of American ideas and beliefs during the period of the founding of the democracy from 1750 to 1780, demonstrates that America has a long heritage behind its social and political philosophy. The excerpts are from the works that represent four different cultural or historical heritage, and they are presented in this order: the classical heritage, the English tradition to 1700, the continental stream, and the eighteenth century, both British and American. Mr. Clough, a former professor of English at the University of Wyoming, provides introductory and explanatory comment throughout the volume. The first book of its kind, it should be particularly useful in American studies programs.